2019
DOI: 10.1590/0104-6632.20190361s20170404
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Equation for Total Reducing Sugars (Trs) Estimation on Sweet Potato and Ethanol Yield Potential

Abstract: Sweet potato is an attractive feedstock for ethanol production due to its high starch content and favorable agronomic characteristics. This paper proposes a simple equation to estimate the total reducing sugars (including glucose from starch) in sweet potatoes based on their moisture content (low cost and simple measurement). It allows the calculation of the ethanol production potential of a given sweet potato mash. According to the equation, the ethanol potential increases non-linearly with increasing concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…The total sugar content of the sweet potato used was 26.93±0.86%, and the experimental cultivation yield was 93.91% (Schweinberger et al, 2019a;Weber et al, 2020b). Hence, for the economic evaluation, a sweet potato with 30% of total sugar was assumed as a reference, and yields of 95% were assumed for both fermentation and distillation processes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total sugar content of the sweet potato used was 26.93±0.86%, and the experimental cultivation yield was 93.91% (Schweinberger et al, 2019a;Weber et al, 2020b). Hence, for the economic evaluation, a sweet potato with 30% of total sugar was assumed as a reference, and yields of 95% were assumed for both fermentation and distillation processes.…”
Section: Resultsmentioning
confidence: 99%
“…The sweet potato used for ethanol production is the cultivar with light yellow peel and pulp. Rotting sweet potatoes were obtained in local fairs (Schweinberger et al, 2019a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher the conversion is, the higher the alcohol yield with lower cost will be, considering there is no need of large amounts of hydrolytic enzymes such as amylases and glucosidases. Schweinberger et al (2019) observed that drier sweet potatoes result in higher ethanol potentials and they made an equation to estimate total reducing sugars based on their moisture content. Results showed that ethanol potential increases non-linearly with increasing concentrations of sweet potato mash in the fermenting medium.…”
Section: Resultsmentioning
confidence: 99%
“…The theoretical potential for ethanol production was calculated using Equation (1): This is an equation proposed by GIMSCOP in a previous study (Schweinberger et al, 2019b), where ethanol concentration (x et,theor ) is calculated as a function of sweet potato moisture (x m_swp , in kg/kg) and amount of potato added (x swp ). The x c_swp value is the proportion of sweet potato (kg) to the added volume of dilution water, so it means x swp (kg)/1 L of dilution water.…”
Section: Ethanol and Distilled Beverage Production Processmentioning
confidence: 99%